FIXED POINT RESULTS FOR JAGGI-TYPE HYBRID CONTRACTION IN JS-MODULAR METRIC SPACES - Zakariyya, Abdulaziz; Shagari, Mohammed Shehu; Mashina, Mohammed Sani (FUDMA JOURNAL OF SCIENCES, 2025)
In this paper, we introduce a new concept of JS-modular metric space and obtain some fixed-point results of hybrid contractions in this setting. Some corollaries that reduce our result to other well-known ideas in the literature are highlighted. An example is constructed to support the established concepts, and to demonstrate the distinction of this research with respect to the existing ones.